Causalidades do produto interno bruto, do consumo de eletricidade e de emissões de CO2 na economia do Brasil e cidades paranaenses - Vieira, Fabrício Diego (2018)
The general objective of this study was to identify how Extreme Values in variables in the financial and ambiental context (per capita Gross Domestic Product, per capita electricity consumption and per capita carbon dioxide – CO2 – emission) can indicate financial instabilities periods. The research is limited to the population of the country (Brazil) and five cities of Paraná (Curitiba, Londrina, Maringá, Ponta Grossa and Cascavel).Therefore, the major research interest was focused on finding information related to Extreme Values and other techniques that are used for interpretation of complex systems currently. The development was based on data collection. The result indicated that extreme events have influence in periods of economic instability. They also evidenced that there is greater correlation in GDP data/electric energy consumption than in GDP data/CO2 emissions or electric energy consumption/CO2 emissions.